2014
DOI: 10.1080/00071668.2014.932335
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Juniper (Juniperus communis) oil on growth performance and meat quality as a natural antioxidant in quail diets

Abstract: 1. This study aimed to evaluate the effects of juniper oil on growth performance and meat quality in quails to determine its use as a safe and natural method to reduce overdependence on the use of antibiotic. 2. A total of 1000 1-d-old Pharaoh (Coturnix coturnix Pharaoh) quails, including both males and females, were divided into 4 groups containing 250 quails and treated as follows: (1) a control group with 0 mg volatile oil/kg diet; (2) 100 mg/kg juniper oil; (3) 150 mg/kg juniper oil and (4) 200 mg/kg junip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 21 publications
1
7
0
1
Order By: Relevance
“…Similarly, juniper essential oil added at 100 and 150 mg/kg feed of quails daily for 42 days during growing and finishing periods induced a significant increase in live weight, live weight gain, and carcass yield. However, feed intake and feed conversion ration were not significantly influenced by such treatments (Yesilbag et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, juniper essential oil added at 100 and 150 mg/kg feed of quails daily for 42 days during growing and finishing periods induced a significant increase in live weight, live weight gain, and carcass yield. However, feed intake and feed conversion ration were not significantly influenced by such treatments (Yesilbag et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Natural antioxidants such as juniper oil have been used in place of synthetic antioxidants to retard lipid peroxidation in stored meat (Yesilbag et al., 2014). Such incorporation of oil is not only increased the shelf-life of stored meat but also improved the meat product quality.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated the chemical compositions of oils acquired from different parts (such as leaves and burls) of the juniper (Adams, ; Hernandez, Martinez, & Villanova, ; Milos & Radonic, ). Its components have been reported to have effects on the intestinal microbiota (Chaves, He, et al, ), growth performance (Yesilbag, Cengiz, Cetin, Meral, & Biricik, ) and egg and meat quality (Cengiz, Yesilbag, Meral, Cetin, & Biricik, ) in farm animals.…”
Section: Introductionmentioning
confidence: 99%
“…The Nuphar lutea was identified as the most active antitrypanosomal plant extract with IC 50 0.42 μg/mL Few additional plant extracts showed activity (IC 50 ) in the range of 2–10 μg/mL. Antioxidant activity has been reported in extracts from Rhus hirta [ 21 ], a different species of Rhus integrifolia ( T. brucei IC 50 - 2.97 μg/mL), Juniperus communis [ 22 ] ( T. brucei IC 50 - 2.40 μg/mL) Sanguisorba officinalis [ 23 ] ( T. brucei IC 50 3.56 μg/mL), Syzygium malaccense [ 24 ] ( T. brucei IC 50 2.76 μg/mL) and Syzygium aqueum [ 25 ] ( T. brucei IC 50 1.84 μg/mL). Eucalyptus citriodora [ 26 ] ( T. brucei IC 50 3.34 μg/mL), Acer rubrum [ 27 ] ( T. brucei IC 50 2.07 μg/mL), Yucca glauca [ 28 ] ( T. brucei IC 50 3.56 μg/mL) plants have also been reported for anticancer activity.…”
Section: Resultsmentioning
confidence: 99%